2019
DOI: 10.1021/acsami.8b22605
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Glue Strategy: Large-Scale Conversion of Clustering-Induced Emission Luminogen to Carbon Dots

Abstract: Carbon dots have wide applications in bioimaging, encryption, sensing, and light-emitting devices, but most preparations of carbon dots require complicated separation and purification steps. Here, a clustering-induced emission luminogen, sodium alginate, was covalently "glued" by ethylenediamine to prepare carbon dots on a 100 g scale, without any separation or purification. The conversion yield was as high as 94.7%. Theoretical calculations suggested that the fluorescence emission of as-prepared carbon dots (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
1
29
0
4
Order By: Relevance
“…High‐resolution scans on C, O, and N elements of N‐CDs exhibited signals for C=O, C−O, and O−Na, indicating that N‐CDs comprised carboxylic sodium moieties. Furthermore, the C−N−C signal of N‐CDs suggested that the hydrothermal treatment formed also amide moieties . Noteworthy, the CDs made from sodium alginate showed the best performance, while those synthesized from poly(acrylic) acid, phytic acid, or carboxylic sodium cellulose did not perform well for the purposes of this study, although they exhibit similar morphology (see Figure S1 in the Supporting Information).…”
Section: Figurementioning
confidence: 85%
“…High‐resolution scans on C, O, and N elements of N‐CDs exhibited signals for C=O, C−O, and O−Na, indicating that N‐CDs comprised carboxylic sodium moieties. Furthermore, the C−N−C signal of N‐CDs suggested that the hydrothermal treatment formed also amide moieties . Noteworthy, the CDs made from sodium alginate showed the best performance, while those synthesized from poly(acrylic) acid, phytic acid, or carboxylic sodium cellulose did not perform well for the purposes of this study, although they exhibit similar morphology (see Figure S1 in the Supporting Information).…”
Section: Figurementioning
confidence: 85%
“…[49] However,t his "top-down" method suffers from problems of limited raw materials and the necessity of using strong acids,w hich may arouse significant environmental concerns.V ery recently,W ang et al proposed am olecular glue strategy for converting clustering-induced emission luminogens into CDs on alarge scale of 100 gper batch with ah igh conversion yield of 94.7 %a nd with no need for subsequent separation and purification steps. [50] This approach offers ac onvenient method for the large-scale production of CDs.H owever,t he quality of the CDs needs to be improved.…”
Section: Other Methodsmentioning
confidence: 99%
“…Very recently, Wang et al. proposed a molecular glue strategy for converting clustering‐induced emission luminogens into CDs on a large scale of 100 g per batch with a high conversion yield of 94.7 % and with no need for subsequent separation and purification steps [50] . This approach offers a convenient method for the large‐scale production of CDs.…”
Section: Large‐scale Production Of Cdsmentioning
confidence: 99%